Progress, challenges, and relevance of the economic policyof Honduras in the government of Xiomara Castro (Journal of Management & Business, 2026)
This article aims to analyze the economic situation in Honduras during the first two years of Pres-ident Xiomara Castro’s government, based on the results generated by the policies implementedto foster economic growth, maintain macroeconomic stability, and address persistent challenges.A mixed approach was applied, integrating the analysis of macroeconomic data from reports bygovernmental and non-governmental institutions, as well as international institutions and orga-nizations. The results reveal that, despite progress in areas such as foreign investment and the re-duction of the fiscal deficit, significant challenges related to corruption, infrastructure, and povertypersist. It is highlighted that the government’s policies have had a positive impact on the country’seconomic stabilization, as evidenced by improvements in some key indicators. The need for signif-icant and continuous efforts to resolve structural problems that limit economic development, suchas weak institutionality and inequality, is also evident. The conclusions underline the importanceof strengthening public administration and the rule of law to consolidate economic progress andensure inclusive and sustainable growth. The implementation of more inclusive and participatorypolicies is recommended for a more equitable distribution of the benefits of economic growth andthe strengthening of democratic governance. This analysis provides a comprehensive overview ofthe Honduran economy, highlighting both achievements and areas requiring urgent attention forthe sustainable development of Honduras.
Keywords: Progress; challenges; economy; Honduras